European Agreement Concerning the International Carriage of Dangerous Goods by Road (ADR): Applicable as from 1 January 2011 - United Nations Economic Commission for Europe (United Nations, 2010)
This authoritative Agreement is intended to increase the safety of international transport of dangerous goods by road. Regularly amended and updated since its entry into force, it contains the conditions under which dangerous goods may be carried internationally. This version has been prepared on the basis of amendments applicable as from 1 January 2011. It contains in particular revised provisions concerning the carriage of dangerous goods packed in limited quantities and the carriage of substances which are toxic by inhalation, new criteria for the classification of environmentally hazardous substances, revised requirements for the construction and testing of pressure receptacles, tanks, battery-vehicles and MEGCs, including conformity assessment and periodic inspection, as well as revised provisions for the training of drivers, the safety obligations of unloaders and instructions in writing to be carried on board the vehicle.